Prevalence and Factors Associated with Musculoskeletal Disorders among Military Personnel Deployed for the Peace Building Process in the Three Southern Border Provinces of Thailand - Payanglee, Kolip; Patthanapreechawong, Chareef; Kuan-akewinyo, Panus; Cheevakul, Anuntasuk; Sukchan, Phnom; Hounkong, Kruawan (Princess of Naradhiwas University Journal, 2019)
Military personnel who perform in the Three Southern Border Provinces of Thailand must stand and patrol for long periods of time. They must perform the same tasks repeatedly. And they carry heavy armaments. In this study, we investigated the prevalence and factors associated with musculoskeletal disorders among 145 military personnel deployed in the Three Southern Border Provinces of Thailand. The data collection tool was the Standard Nordic Questionnaire (Thai version). Chi-square test, correlated data, and descriptive statistics were used to describe parameters and prevalence. The result found that the overall prevalence of musculoskeletal disorders among the troops was as high as 70.34%, while the prevalence 12 months before for low back pain (35.87%), hips or thighs pain (32.41%), shoulders pain (30.34%), knees pain (29.66%), yielded high levels. In addition, the prevalence 7 days before showed elbows pain (58.82%), upper back pain (56.25%), low back pain (51.92%) and shoulders pain (45.56%). Moreover, the results revealed that the number of working years and working hours per week were in statistically significant correlation with low back pain among military, while shoulder pain was in statistically significant correlation with the number of working hours per week. All finding in this study can be used as preliminary data in prevention program development for musculoskeletal disorders among military personnel deployed for the peace building process in the Three Southern Border Provinces of Thailand.